2013
DOI: 10.1039/c3cc39237f
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic-field-induced deposition to fabricate multifunctional nanostructured Co, Ni, and CoNi alloy films as catalysts, ferromagnetic and superhydrophobic materials

Abstract: A novel and facile magnetic-field-induced deposition process was put forward to fabricate nanostructured Co, Ni and CoNi alloy films supported on Cu foil, which are multifunctional nanomaterials with wide applications in different areas due to their ferromagnetic and superhydrophobic properties, as well as their excellent catalytic performance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
33
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(35 citation statements)
references
References 21 publications
2
33
0
Order By: Relevance
“…The metal‐free catalytic reduction of Nip to 4‐aminophenol using NaBH 4 as the reductant mediated by N‐doped graphene (NG) was reported by Chen group . The undoped graphene materials did not possess any catalytic activity; while the activity of the NG is comparable with some of the previously reported metallic catalysts . In situ FTIR experiment demonstrated that Nip ions adsorb to NG via the hydroxyl groups but not the nitro.…”
Section: Reductionmentioning
confidence: 84%
“…The metal‐free catalytic reduction of Nip to 4‐aminophenol using NaBH 4 as the reductant mediated by N‐doped graphene (NG) was reported by Chen group . The undoped graphene materials did not possess any catalytic activity; while the activity of the NG is comparable with some of the previously reported metallic catalysts . In situ FTIR experiment demonstrated that Nip ions adsorb to NG via the hydroxyl groups but not the nitro.…”
Section: Reductionmentioning
confidence: 84%
“…This also confirms the formation 4‐AP as a sole product of the reaction. The characteristic peaks of the 4‐AP are IR: (ν max =cm −1 ): 3423; 3340 (NH 2 ); 3190 (OH) …”
Section: Catalytic Reduction Of 4‐np To 4‐apmentioning
confidence: 99%
“…Fig. [20][21][22][23][24][25][26][27][28][29] Spongy/dendritic structures are renowned for their superior catalytic activity and efficient utilization of catalyst due to special characteristics of alloys and dendritic structures. The Cu-Pt nanodendrites apparently possess a dense branching morphology, while the Cu-Pd and Cu-Au nanodendrites appear to be more symmetrical.…”
Section: (B D and F))mentioning
confidence: 99%
“…The Cu-Pt nanodendrites apparently possess a dense branching morphology, while the Cu-Pd and Cu-Au nanodendrites appear to be more symmetrical. 21,[25][26][27][28][29][30][31][32] The conversion of 4-nitrophenolate ions to 4-AP by the spongy/dendritic structures was monitored by UV-visible spectroscopy, as shown in Fig. The presence of noble metal in the Cu-based dendritic structures is confirmed through EDS studies (Fig.…”
Section: (B D and F))mentioning
confidence: 99%